Modeling of Forest and Land Fires Risk Level and Zone Using GIS in Kapuas Tengah Sub Basin, West Kalimantan Province - Iin Arianti; Naik Sinukaban; I Nengah Surati Jaya (Jurnal Manajemen Hutan Tropika, 2007)
In the last 2 decades, forest and land fires in Indonesia have become a serious problem at national, regional, and even international levels. The smoke of the fires gave a negative impact on human activities and health and in turn coused economical and social loss. In addition, the haze pollution has become a serious problem internationally. This study was conducted to establish a risk model of forest and land fire in Kapuas tengah watershed, Kalimantan Barat Province. The model was based on scoring and weighting of bio-phisycal and human activity factors. Rangking method and Composite Mapping Analysis (CMA) were used to establish the model. The result showed that the accuracy of model by ranking method to determine the risk level and zone of forest and land fire was only 62,4% in Kapuas Tengah watersheed. Therefore, the model was not good enough to represent actual condition in the field. The accuracy of model using CMA method could be used to determine risk level and zone of forest and land fire. The CMA method showed that the Kapuas Tengah watershed consisted of 1,051,029.4 ha high risk, 379,307.0 ha of moderate and 195,010.7 ha of low vulnerable. The risk map can be used for early warning system to prevent forest and land fires.Keywords: forest and land fires, composite mapping analysis, rangking method, fire risk map